CREATING ALTERNATIVE ROUTES IN THE DOMESTIC LOGISTICS PROCESS ACCORDING TO COMPETITION PRIORITIES (Third Sector Social Economic Review, 2024)
In this research, for demand-based production, the North West Corner Method (NWCM), Vogel's Approach Method (VOGEL), Minimum Cost Method (MCM), Stepping Stone Method (SSM) and Modified Distribution Method (MODİ) were used in production management. It is aimed to make and compare cost analyzes for internal logistics processes using models. According to the results obtained in the study, there are no statistically significant differences in terms of cost in the pairwise comparisons of NWCM, MCM and VOGEL methods (p>0.05). According to the results of comparing the main models with hybrid models other than their own hybrid models, the differences between MCM and NWCM-SSM, the differences between MCM and VOGEL-SSM, and the differences between VOGEL and NWCM-SSM are statistically significant (p
Keywords: Production management; alternative models; internal logistics; demand; cost.